2005
DOI: 10.1002/ajmg.b.30254
|View full text |Cite
|
Sign up to set email alerts
|

Genetic liability to schizophrenia or bipolar disorder and its relationship to brain structure

Abstract: Bipolar disorder and schizophrenia are highly heritable conditions that are associated with structural brain abnormalities. Although brain abnormalities are found in the well relatives of people with schizophrenia, the extent to which genetic liability relates to brain structure in either disorder is still unclear. This study sought to ascertain the effects of genetic liability to schizophrenia and bipolar disorder on white and grey matter volume in patients with these diagnoses and their well relatives. Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 47 publications
5
81
0
Order By: Relevance
“…McDonald et al (2004) reported a negative association between genetic risk for BD and gray matter volume in the right medial frontal gyrus, anterior cingulate gyrus, and striatum. However, McIntosh et al (2006) did not find any effect of genetic liability in relatives from families multiply affected with BD. Both research groups conducted further analyses on their samples.…”
Section: Introductionmentioning
confidence: 63%
“…McDonald et al (2004) reported a negative association between genetic risk for BD and gray matter volume in the right medial frontal gyrus, anterior cingulate gyrus, and striatum. However, McIntosh et al (2006) did not find any effect of genetic liability in relatives from families multiply affected with BD. Both research groups conducted further analyses on their samples.…”
Section: Introductionmentioning
confidence: 63%
“…2 These findings have been associated with increased genetic liability to psychosis, albeit to unidentified loci 4 and by functional imaging studies in patients with schizophrenia 27,28 and those at high risk for genetic reasons. 29 These studies further implicate white matter disconnectivity in psychosis, although they cannot determine whether this is because of reduced axonal number, increased axonal disorganization or dysmyelination.…”
Section: Discussionmentioning
confidence: 95%
“…Using T 1 -weighted MRI, and DTI, abnormalities of white matter density and integrity have been shown in the ALIC in schizophrenia, 2,3 bipolar disorder 2,26 and their unaffected relatives. 2 These findings have been associated with increased genetic liability to psychosis, albeit to unidentified loci 4 and by functional imaging studies in patients with schizophrenia 27,28 and those at high risk for genetic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations